PELAKSANAAN KEWAJIBAN ORANG TUA TERHADAP ANAK PECANDU GAME ON-LINE DI JALAN SALAK RAYA KOTA BENGKULU DALAM PERSPEKTIF HUKUM ISLAM - Firdaus, Julian (UIN Fatmawati Sukarno Bengkulu, 2018)
In this research there are several problems 1). How the rights and obligations of parents to children online game addicts. 2). How to review Islamic law against children online game addicts at Warnet BM Jalan Salak Raya, Bengkulu City. To answer the problem of research above conducted field research (field research) using qualitative descriptive approach method. The data collected by observation method, interview and documentation, from the source of the informant that the author set based on purposive sampling. The results of the study explain, first Rights and obligations of parents to the child has not been done due to various factors, among others, busy work so that the lack of attention to children who cause children abandoned. Second Every child should be good and obedient to the parents. The child is not justified in being abusive to both parents. Therefore, every child must have obligations and responsibilities to parents who have raised and nourished them from child- hood to adulthood. Children should keep the rights of parents, children should also maintain morals as stock in running Ikhsan against both parents